Relationship Compliance with the Use of PPE with Confirmed Covid 19 to Nurses in Covid 19 Isolation Ward at Islamic Hospital Darus Syifa’ Surabaya: Hubungan Kepatuhan Penggunaan APD Dengan Kejadian Terkonfirmasi Covid 19 Pada Perawat di Ruang Isolasi Covid 19 di Rumah Sakit Islam Darus Syifa’ Surabaya - R, Lina Madyastuti; Prameswari, Riski Dwi; Basri, Ahmad Hasan; laili, Nur (Universitas Muhammadiyah Sidoarjo, 2022)
Personal protective equipment (APD) is a piece of equipment that must be used when working in accordance with work hazards and risks to maintain personal safety in dealing with Covid 19 patients. The factor causing non- compliance in using level 3 complete APD is lack of vigilance in protecting your self because when using level 3 APD you feel uncomfortable, irritable,and not free to take action.This study aims to determine the relationship between compliance with the use of APD with confirmed cases of Covid 19 for nurses. This research used cross sectional method. The sample technique used was total sampling . The population in this study was 23 respondents. The independent variable was compliance’s nurses used of Personal protective equipment (APD) and the dependent variable used was the nurse was confirmed COVID 19 in the COVID 19 isolation ward. The data collection used was questionnaires, observations, and the results of the Covid 19 antigen swab. This study used the chi- square test with a significance level of p<0,05. The results of this study indicate that there was a relationship between compliance with the use of APD whit confirmed cases of COVID 19 in nurses in the COVID 19 isolation ward, the results obtained are R = 0.154 (p = 0.00) then it means that H1 there was a relationship between compliance with the use of Personal protective equipment (APD) with confirmed cases of COVID 19 in nurses in COVID 19 isolation ward. The higher the level of compliance with the use of APD by nurses in the COVID 19 isolation ward, the lower the number of confirmed cases of COVID 19 with evidence of negative antigen swab results. It is hoped that nurses in the COVID 19 isolation ward will always be vigilant and comply with the use of level 3 APD and always seek information related to the service of the risk of infection contracting COVID 19 through mass media,seminars, and training.